Can be Explained the Moroccan Growth of Public Spending by the Demand Approach? - Kchirid, El Mustapha; Adouka, Lakhdar; Darraji, Aissa; Kerbouche, Mohamed (Richtmann Publishing, 2012)
The objective of this paper is to explain the growth of public spending by the approach of the demand for public goodsin Morocco from 1970 to 2010, to test the veracity of Wagner's law for the Moroccan economy by an approach demand, to verifythe positive effect between the share of public expenditure to GDP ratio and the following variables: the per capita income,population, urbanization, degree of economic openness, the effect of Baumol and macroeconomic stability. We concluded fromour study that Wagner's law holds for the Moroccan economy. Our model confirms the positive effect between the share ofpublic expenditure to GDP ratio and the following explanatory variables: per capita income, the degree of economic openness,the effect of macroeconomic stability and the effect of Baumol ..We also concluded from our study that there is a feedbackrelationship between public spending and per capita income using the Granger causality test.